Wali al-Nikāḥ Hierarchies in Theory and Practice: Disputes, Authority, and Social Reality in Indonesian Muslim Communities - Muhammad Sirojudin Sidiq; Andi Ali Akbar; Anggita Vela; Muhammad Farid Zulkarnain (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
This article examines the problematic social practices related to the appointment of Wali al-Nikāḥ (marriage guardians) in Kotagajah Subdistrict, Central Lampung Regency, Indonesia. The focus lies on conflicts surrounding the rejection of Wali al-Nasab (lineal guardians) by the bride's family, disputes among multiple guardians within the hierarchical structure, and unauthorized delegation of wali. This study explores the tension between the normative framework of Islamic law regarding Wali al-Nikāḥ and the lived realities of marriage practice at the community level. To address this issue, a qualitative fieldwork approach was employed using a socio-legal lens. Data were collected through interviews with penghulu (marriage registrars), religious leaders, and families who have experienced guardianship disputes, supported by administrative documents from the Office of Religious Affairs (KUA) and references from classical fiqh texts and Indonesian marriage law. The findings reveal various forms of conflict in marriage proceedings, including the moral disqualification of biological fathers, internal family disputes over rightful guardianship, and administrative manipulations such as